2011
DOI: 10.1063/1.3638698
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of wurtzite/zinc-blende heterostructures in GaN nanowires

Abstract: The optical and structural properties of wurtzite GaN nanowires containing zinc-blende GaN inclusions of different thicknesses are investigated. Micro-photoluminescence spectra of single nanowires exhibit a series of narrow emission peaks with linewidth as low as 0.8 meV in the interval 3.1-3.42 eV. The peak energy blue-shifts with increasing excitation power following a $I 1/3 law due to the progressive band filling and to the screening of the internal field. The quantum confinement in these type-II crystal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 33 publications
11
50
0
Order By: Relevance
“…well below the ZB NBE emission at 3.27 eV. These peaks originate from ZB segments in the WZ crystal, in line with similar observations by Skromme et al [29] and Jacopin et al [33]. Taking the polarization fields of 2.5 MV/cm (P sp = −0.022 C/m 2 ) determined in [32], we have calculated the emission energies for cubic segments up to a thickness of 3 nm.…”
Section: Zinc-blende Segmentssupporting
confidence: 85%
See 1 more Smart Citation
“…well below the ZB NBE emission at 3.27 eV. These peaks originate from ZB segments in the WZ crystal, in line with similar observations by Skromme et al [29] and Jacopin et al [33]. Taking the polarization fields of 2.5 MV/cm (P sp = −0.022 C/m 2 ) determined in [32], we have calculated the emission energies for cubic segments up to a thickness of 3 nm.…”
Section: Zinc-blende Segmentssupporting
confidence: 85%
“…However, the linewidth obtained for the donor-bound exciton in the microcrystals investigated here amounts to only 1 meV [69] indicating that the BSF emission still suffers some form of broadening. Jacopin et al [33] reported a linewidth down to 0.8 meV on ZB/WZ quantum wells in GaN nanowires, and even lower values (< 0.5 meV) have been reported for GaAs and InP [38,61].…”
Section: Other Influences On the Emission Energiesmentioning
confidence: 91%
“…The peak energy, however, blue-shifts clearly with increasing power for the I 1 transition, while being nearly constant for X. The overall phenomenology reported for transition I 1 is compatible with that attributed to basal stacking faults (BSFs) [14,15]. Non-polar QDs can be often crossed by BSFs which are common in a-plane AlN, as shown in TEM image of the upper inset of Fig.…”
Section: Resultssupporting
confidence: 70%
“…Furthermore, reduced growth temperatures are required for the incorporation of In. This reduced growth temperature may increase the point defect density and can facilitate the nucleation of zinc-blende (ZB) segments [9,11,33,34]. The manifestation in the luminescence spectra of both intrinsic and extrinsic point defects as well as ZB segments will be presented in the following paragraphs.…”
Section: Spatially and Spectrally Resolved Emission Within Single Nwsmentioning
confidence: 98%